Construction of Social Reality for Physical Distancing During the COVID-19 Pandemic - Christin, Maylanny; Hidayat, Dasrun; Rachmiatie, Atie (Jurnal Komunikasi, 2021)
The focus of the research is communication behavior in the Physical Distancing phase during COVID-19. Physical Distancing is a government policy intended to reduce the spread of COVID-19. The research objective was to analyze the knowledge and communication behavior of the people. The method used is phenomenology with a qualitative approach. Involving the people of Bandung city as research informants as many as 11 people. The technique of collecting data through online interviews is that physical distancing is still in place. The results showed that the physical distancing phase of the community's communication behavior can be categorized into three groups including active, sympathetic, and indifferent groups. Active group means being concerned with finding information and implementing Physical Distancing policies. The sympathy group is receiving Physical Distancing information, but not fully carrying out Physical Distancing. Informant groups are indifferent or passive informants in seeking information and do not carry out Physical Distancing. Another communication behavior that the Physical Distancing phase activities is carried out online using digital media. Informants admit that Physical Distancing activities have changed the dimension of interpersonal communication which requires the presence of distance, but the Physical Distancing phase has turned virtual. This communication behavior builds a shared experience that online communication encourages the formation of virtual relationships. The results of this study are expected to contribute to online communication competence as an effort to maintain the quality of communication even though it is done online. Fokus penelitian adalah perilaku komunikasi pada fase Physical Distancing selama COVID-19. Physical Distancing merupakan kebijakan pemerintah yang dimaksudkan untuk mengurangi penyebaran COVID-19. Tujuan penelitian untuk menganalisis pengetahuan dan perilaku komunikasi masyarakat. Metode yang digunakan fenomenologi dengan pendekatan kualitatif. Melibatkan masyarakat kota Bandung sebagai informan penelitian sebanyak 11 orang. Adapun teknik pengumpulan data melalui wawancara daring mengingat masih diberlakukannya Physical Distancing. Hasil penelitian menunjukkan bahwa perilaku komunikasi masyarakat fase Physical Distancing dapat dikategorikan dalam tiga kelompok meliputi kelompok aktif, simpati, dan acuh. Kelompok aktif artinya peduli dengan mencari informasi dan menjalankan kebijakan Physical Distancing. Kelompok simpati yaitu menerima informasi Physical Distancing, namun tidak sepenuhnya menjalankan Physical Distancing. Kelompok informan acuh atau informan pasif dalam mencari informasi dan tidak menjalankan Physical Distancing. Perilaku komunikasi lainnya bahwa aktivitas fase Physical Distancing dilakukan secara daring dengan menggunakan media digital. Informan mengakui bahwa aktivitas Physical Distancing telah merubah dimensi komunikasi interpersonal yang mensyaratkan kehadiran jarak, namun fase Physical Distancing berubah menjadi virtual. Perilaku komunikasi tersebut membangun pengalaman bersama bahwa komunikasi daring mendorong terbentuknya hubungan virtual. Hasil penelitian ini diharapkan dapat berkontribusi terhadap kompetensi komunikasi daring sebagai upaya menjaga kualitas komunikasi meskipun dilakukan secara daring.